An Introduction to Mathematics for Social Justice. Issue 3 (21st April 2019) - Buell, Catherine A.; Shulman, Bonnie
Abstract: In this introduction to the PRIMUS Special Issue on Mathematics for Social Justice we provide a brief history of social justice in the context of undergraduate mathematics pedagogy and explain the purpose and motivation behind this movement in undergraduate education.